TRANSFORMASI DIGITAL DAN PEMANFAATAN TEKNOLOGI DALAM MENINGKATKAN EFISIENSI DAN TRANSPARANSI KINERJA INSTANSI PEMERINTAH - Hwihanus Hwihanus; Maulidah Narastri; Muhammad Taufiq Hidayat (J-MACC, 2025)
Digital transformation has become a strategic agenda in strengthening the governance of government institutions. This study aims to analyze the impact of digital technology utilization on improving operational efficiency and performance transparency in government agencies, particularly in the context of implementing the Electronic-Based Government System (SPBE). A quantitative approach was employed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). Data were collected through questionnaires distributed to institutional personnel using purposive sampling. Preliminary analysis results indicate that the use of digital technology has a significant positive effect on both efficiency and transparency, although challenges remain, such as human resource readiness and system integration. This research contributes theoretically by integrating the frameworks of New Public Management, the Technology Acceptance Model, and Good Governance, while also offering practical implications in the form of adaptive digitalization strategy recommendations for the public sector.